'It was really dark': the experiences and preferences of people with aphasia to manage mood changes and depression. Issue 1 (2nd January 2020) - Baker, Caroline; Worrall, Linda; Rose, Miranda; Ryan, Brooke
ABSTRACT: Background : People with aphasia are at high risk of depression with the majority fulfilling depression diagnostic criteria up to one year post-stroke. There is a lack of psychological care to prevent and treat depression and address the communication disability associated with aphasia. Translating a framework of stepped psychological care after stroke may potentially address treatment gaps and improve rehabilitation outcomes. This multidisciplinary framework is usually composed of level 1 to 4 interventions that match the person's level of need and severity of symptoms. However, the perspectives of people with aphasia regarding stepped psychological care, mood changes, depression and current practice is extremely limited in the research evidence. Aims : To describe, from the perspective of people with aphasia: a) the experience of mood changes, depression and current practice after post-stroke aphasia; and b) preferences within a stepped psychological care approach. Method & Procedures : Ten people with aphasia participated in two semi-structured interviews each, within a maximal variation sample (severity of aphasia, presence or not of possible depression, transition phase of care). Video data from the 20 interviews were transcribed for speech and non-speech communication and analysed using Interpretive Description. Outcomes & Results : All participants self-reported mostly negative mood changes after aphasia whether they were identified as depressed or not on the SADQ10. Three core themes were derived: 1) the onset of stroke and aphasia is a traumatic event resulting in mood difficulties and depression; 2) people with aphasia are trying to work through communication and mood difficulties with limited psychological support and services in stroke rehabilitation; 3) positivity, supported communication and access to individually tailored therapy would be essential to people with aphasia through stepped psychological care. 10 sub-themes were also identified. Conclusions : This study demonstrates that the onset of post-stroke aphasia is traumatic with negative mood changes impacting ability to participate in stroke rehabilitation. Within this context, it was evident that all participants experienced mood changes but had not participated in stepped psychological care in stroke rehabilitation. Some had experienced elements of psychological care. Stepped psychological care is recommended for people with aphasia.